Uterine leiomyoma in the pediatric population: literature review - Zaira Kh. Kumykova; Zalina K. Batyrova; Tamara G. Dilanyan; Anna I. Turchinets; Elena V. Uvarova (IP Berlin A.V., 2023)
Uterine fibroids are the most common benign neoplastic tumor of the uterus, occurring in adolescents with a frequency of less than 1%. According to literature data, 87.5% of young patients, as a rule, have a variety of symptoms, the most frequent of which is abnormal uterine bleeding, anemizing the patient, abdominal pain, abdominal enlargement in volume. Diagnosis in adolescent girls may be difficult, due to the rarity, as well as the presence of some limitations in the echographic examination performed, as a rule, by transabdominal access. Methods of treating leiomyomas in women are well known and are widely described in clinical guidelines ranging from surgical to medicinal, however, they are not standardized for the pediatric population. Currently, no more than 25 clinical observations have been described in the literature, which indicates the importance of accumulating clinical data in order to develop an optimal clinical approach aimed at preserving reproductive function in such patients.